Предмет: Математика,
автор: sashapichugina
Решите уравнение
Ответы
Автор ответа:
1
x+2=t
x-3=t-5
3x-4=3t-10
(√t+√(t-5))^2=√(3t-10)^2
t+t-5+2√(t^2-5t)=3t-10
2√(t^2-5t)=t-5
4(t^2-5t)=t^2-10t+25
4t^2-20t=t^2-10t+25
3t^2-10t-25=0
D=100+12*25 = 20^2
t=(10+/-20)/6 = 5, -5/3
x=3
x-3=t-5
3x-4=3t-10
(√t+√(t-5))^2=√(3t-10)^2
t+t-5+2√(t^2-5t)=3t-10
2√(t^2-5t)=t-5
4(t^2-5t)=t^2-10t+25
4t^2-20t=t^2-10t+25
3t^2-10t-25=0
D=100+12*25 = 20^2
t=(10+/-20)/6 = 5, -5/3
x=3
sashapichugina:
спасибо огромное) а можете ещё с одним помочь?
Похожие вопросы
Предмет: Математика,
автор: zzz7322
Предмет: Математика,
автор: melnichenko124578
Предмет: Русский язык,
автор: alinaprostakova13
Предмет: Биология,
автор: Анжела789
Предмет: Математика,
автор: alenashafeeva